Program Bimbingan Komunikasi Dalam Menunjang Pemasaran Bisnis Online Pada Siswa Smk Negeri 1 Rantau Utara Jurusan Pemasaran - Budi Febriani; Usmala Dewi Siregar; Nova Jayanti Harahap; Pristiyono Pristiyono; Meisa Fitri Nasution (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
Online shopping is a communication technology that utilizes the internet with various services. It saves time when working without having to meet in person. Consumers who shop at online stores can easily access the online store they want, see the selection of goods and prices purchased, find out the quality of goods from buyer comments and pay. This study discusses the strategy of using online stores as a digital marketing communication tool. In this study, quantitative and qualitative descriptive methods were used. In addition, this study also uses library research techniques to obtain information and reference materials. Data collection procedures were carried out by observing through online shops and library research. The type of data used is qualitative. From the results of the interviews and the data that has been collected, it can be concluded that the diagram showing the color red as Instagram users is more widely used around the school environment so that it greatly influences the ease of online business strategy communication in the North Rantau Vocational High School 1 environment. Based on the results of research and discussion, Instagram can be used as a digital marketing communication tool. The marketing strategy through the online media business is actually quite difficult to penetrate the market in Indonesia. This is due to the many differences in consumers in Indonesia, starting from how to buy, assessing products, advertising, economic conditions, cultural differences and technological developments, which are a challenge for e-commerce